2009
DOI: 10.1063/1.3205884
|View full text |Cite
|
Sign up to set email alerts
|

Edge turbulence measurements in electron-heated Helically Symmetric Experiment plasmas

Abstract: This paper presents edge measurements utilizing Langmuir probes to characterize plasma turbulence in the Helically Symmetric Experiment (HSX) [F. S. B. Anderson et al., Fusion Technol. 27, 273 (1995)]. Normalized density and potential fluctuations exhibit strong intensities but are comparable to mixing length estimates using measured correlation lengths. The correlation lengths are isotropic with respect to radial and poloidal directions and follow local (gyro-Bohm) drift wave expectations. These observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The structure of eigenmodes plays an important role in determining the effectiveness of nonlinear energy transfer from unstable to damped eigenmodes in turbulent saturation physics (Terry et al 2006;Hatch et al 2009). In a configuration like HSX, where eigenmodes are more extended along the field line, both the nonlinear coupling between eigenmodes and therefore the nonlinear transfer of energy to stable modes is more efficient (Hegna et al 2018), allowing for lower saturated heat flux levels.…”
Section: Eigenmode Structurementioning
confidence: 99%
See 2 more Smart Citations
“…The structure of eigenmodes plays an important role in determining the effectiveness of nonlinear energy transfer from unstable to damped eigenmodes in turbulent saturation physics (Terry et al 2006;Hatch et al 2009). In a configuration like HSX, where eigenmodes are more extended along the field line, both the nonlinear coupling between eigenmodes and therefore the nonlinear transfer of energy to stable modes is more efficient (Hegna et al 2018), allowing for lower saturated heat flux levels.…”
Section: Eigenmode Structurementioning
confidence: 99%
“…HSX has shown that even with the reduction in neoclassical heat transport (Canik et al 2007), there is still an additional component to the experimentally-inferred electron heat transport that is thought to be due to trapped-electron-mode (TEM) turbulence (Guttenfelder et al 2009;Weir 2014;Faber et al 2015). In general, turbulence accesses free energy in thermodynamic forces which subsequently produces turbulent transport fluxes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here ṽ and V f l denote the fluctuating components of local single-fluid × E B velocity and measured floating potential in time, respectively, on the timescale of a few turbulence decorrelation times or less (τ ≈ 10 d μs in these experiments). It is assumed that the fluctuations are purely electrostatic, which should be valid in these low β HSX plasmas [20] (β < − 10 4 where probe measurements are made). This formulation for the fluctuating quantities accounts for any mean T e gradients that may exist between the pins, as the Ṽ f l quantities are mean-free, but it does not account for fluctuating components of T e on the scale length of the probe tip separation.…”
Section: Reynolds Stress Probe Designmentioning
confidence: 99%
“…It is important to note that the ripple in the edge of HSX, even in the optimized configuration, is an order of magnitude larger than NSTX with RMP coils. Turbulence has also been shown to increase with minor radius [20] and so the turbulence-free, perfectly quasi-symmetric model in neoclassical transport does not apply [5,10]. Previous studies in HSX have shown that for the QHS configuration, thermal transport is dominated by anomalous rather than neoclassical effects throughout the plasma [18,21].…”
Section: Nuclear Fusionmentioning
confidence: 99%